Cell signaling pathways in the adrenal cortex: Links to stem/progenitor biology and neoplasia. (15th April 2017) - Penny, Morgan K.; Finco, Isabella; Hammer, Gary D.
Abstract: The adrenal cortex is a dynamic tissue responsible for the synthesis of steroid hormones, including mineralocorticoids, glucocorticoids, and androgens in humans. Advances have been made in understanding the role of adrenocortical stem/progenitor cell populations in cortex homeostasis and self-renewal. Recently, large molecular profiling studies of adrenocortical carcinoma (ACC) have given insights into proteins and signaling pathways involved in normal tissue homeostasis that become dysregulated in cancer. These data provide an impetus to examine the cellular pathways implicated in adrenocortical disease and study connections, or lack thereof, between adrenal homeostasis and tumorigenesis, with a particular focus on stem and progenitor cell pathways. In this review, we discuss evidence for stem/progenitor cells in the adrenal cortex, proteins and signaling pathways that may regulate these cells, and the role these proteins play in pathologic and neoplastic conditions. In turn, we also examine common perturbations in adrenocortical tumors (ACT) and how these proteins and pathways may be involved in adrenal homeostasis. Highlights: In this literature review, we discuss evidence for stem/progenitor cells in the adrenal cortex. We also discuss cellular signaling pathways critical to the adrenocortical stem/progenitor niche. We address the role of adrenocortical stem/progenitor signaling pathways in pathologic and neoplastic conditions. We examine perturbations in adrenocortical tumors (ACT) that may be involved in adrenal homeostasis.